CORRELATION BETWEEN EMOTION REGULATION AND SOCIAL PROBLEM - SOLVING SKILLS DURING THE COVID-19 PANDEMIC - Pīpkalēja, Linda; Paiča, Inese (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
The research objective was to investigate the relationship between emotion regulation and social problem-solving skills among adults during COVID-19 pandemic. The theoretical basis of the research is the Adaptive Coping with Emotions Model and Social problem-solving model. The participants of the study were 2608 Latvian residents aged 18 to 75 years (M = 46.4, SD = 13.9). Respondents filled in a socio-demographic survey, Emotion Regulation Skills Questionnaire and Social Problem-Solving Inventory-Revised version. The results revealed the relationship between emotion regulation and social problem-solving skills in adults, the closest relationship between positive problem orientation, rational problem-solving style and total emotion regulation skills. There are differences in total emotion regulation skills and almost all social problem-solving skills subscales between age groups, except for impulsive problem-solving, and differences in total emotion regulation skills and almost all social problem-solving skills subscales between groups with different levels of education, except for avoidant problem-solving. It is concluded that the development of emotion regulation skills can contribute to the improvement of social problem-solving skills, and with changes in age and level of education, the ability to regulate emotions and to cope with various social problems changes.